On a Question of a Role of the Printing Book in Besieged Leningrad in days of the Great Patriotic War - Galina Nikolaevna Pitulko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Article is devoted to the role of printed books in Leningrad’s blockade of the period of the Great Patriotic War. There are some examples of the most interesting editions, including ones of Leningrad’s blockade in the article. It should be noted, that printed book has important ideological role. The author considers this theme on the basis of book collection of the Library of Russian Academy of Sciences.